Transverse Momentum Distributions in AuAu and dAu Collisions at sNN=200 GeV. (10th April 2014) - Wang, Li-Li
Abstract : We study the transverse momentum distributions of identified particles produced in Au + Au and d + Au collisions at S N N = 200 GeV. The Tsallis description is applied in the multisource model. The results are compared with the experimental data in detail. We obtain some information of the thermodynamic properties of matter produced in the collisions. The difference of the transverse momentum distributions in Au + Au and d + Au collisions is not significant.